Comparative analysis of implantable cardioverter-defibrillator efficacy in ischemic and non-ischemic cardiomyopathy in patients with heart failure - Emre Demir; Mehmet Ruhat Köse; Evrim Şimşek; Mehmet Nurullah Orman; Mehdi Zoghi; Cemil Gürgün; Sanem Nalbantgil (Scientific Reports)
Abstract The role of implantable cardioverter-defibrillators (ICDs) in preventing sudden cardiac death in heart failure patients with reduced ejection fraction (HFrEF) is well-established, particularly in ischemic cardiomyopathy (ICM). However, the benefit of ICDs in non-ischemic cardiomyopathy (NICM) remains uncertain. This study aimed to compare the efficacy of ICDs in HFrEF patients with ischemic versus non-ischemic cardiomyopathy. A total of 1271 patients with a left ventricular ejection fraction (LVEF) ≤ 35% were analyzed, of whom 46.3% received ICD implantation. The primary endpoint was a composite of all-cause mortality, advanced heart failure therapies, and ventricular arrhythmias. In patients with ICM, ICD implantation significantly reduced the risk of the primary endpoint (HR 0.717, 95% CI 0.595–0.861; p = 0.0004). However, in NICM patients, ICD therapy did not significantly reduce mortality or ventricular arrhythmias (HR 0.767, 95% CI 0.573–1.026; p = 0.074). Among 103 patients whose LVEF improved above 35% and who were excluded from the primary analysis, ICD implantation was associated with a survival advantage in NICM (HR 0.645, 95% CI 0.478–0.870; p = 0.0041). In NICM patients, independent predictors of the primary endpoint included NYHA class III–IV (HR 1.934, 95% CI 1.302–2.871; p = 0.001), moderate to severe mitral regurgitation (HR 1.956, 95% CI 1.224–3.126; p = 0.005), lower TAPSE (HR 0.945, 95% CI 0.904–0.987; p = 0.011), and elevated NT-proBNP (log-transformed) (HR 1.531, 95% CI 1.074–2.183; p = 0.019). A multivariate risk score developed through logistic regression in NICM patients with LVEF < 50% demonstrated high predictive accuracy for the primary outcome (AUC: 0.819, 95% CI 0.778–0.856). In conclusion, while ICDs confer clear survival benefits in ICM, their efficacy in NICM remains uncertain. Refinement of patient selection criteria, particularly in NICM, is warranted as modern heart failure therapies continue to evolve.